The impact of vitamin E, vitamin B6, and niacin intake on cataract incidence based on NHANES 2005-2008 data - Zhuang, Guo-Bin; Li, Xiang; Wu, Shi-Nan; Zhang, Si-Qi; Zhang, Zhi-Jie; Dong, Nuo (Frontiers in Nutrition, 2024)
Our study demonstrates significant inverse associations between higher intakes of vitamin E, vitamin B6, and niacin and a reduced risk of developing cataracts, especially in high-intake groups. This suggests a new nutritional strategy for cataract prevention.We uncovered nonlinear inverse relationships between vitamin E intake and cataract risk, providing fresh perspectives on the complex interactions between vitamin consumption and eye health.The findings support dietary adjustments to increase specific vitamin intakes as a potential strategy for cataract prevention and management, laying a scientific foundation for subsequent clinical trials and public health recommendations.